Peace Education and Religion: Perspectives, Pedagogy, Policies, edited by Marcia Hermansen, Ednan Aslan, Evrim Erşan Akkılıç. Springer VS, Wiesbaden, 2022. XII, 530 pp. https://doi.org/10.1007/978-3-658-36984-2 - Anna Aleksanyan (Journal of Political Science: Bulletin of Yerevan University)
In this book, various authors comparatively analyze the controversial issues of peace education and religion from the point of view of pedagogy and politics. In this context, the authors note that the modern world is becoming increasingly open and at the same time increasingly complex, fragile, unstable and aggressive. Therefore, the need for humanity to protect itself and future generations from the cruelty and violence of those massive scales that have horrified: the most brutal wars, protracted armed conflicts; terrorism; daily encounters with various mental pathologies, disorders, antisocial behavior and dysfunctional relationships, prejudices and discrimination; mass cases of domestic violence, thereby requiring civiliarchic and democratic countries to seek mechanisms to reduce them. The authors in their research draw attention to the fact that peace education is an effective way to prevent and reduce all types of violence, from global threats to peace to everyday conflicts. It is built on the basis of key, comprehensive social and humanistic values. In this sense, the goal of modern peace education is the development of a culture of peace in all its manifestations, since the content of peace education includes a wide range of knowledge from concepts of peace to religious and environmental issues. This knowledge is included in the content of both individual peace education courses of different focus, and in various educational areas.